2020
DOI: 10.1080/10942912.2020.1733600
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dough rheological and steamed bread fortified with extruded purple sweet potato flour

Abstract: Addition of purple sweet potato flour has a negative effect on the technological characteristics of steamed bread. The present study researches the potential of extruded purple sweet potato flour (EP) in improving the quality of composite dough and steamed bread. Compared to unextruded purple sweet potato flour (UP), addition of EP significantly increased dough thermal temperatures and decreased the freezable water content, indicating that it enhanced the binding of dough components with water molecules. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…For the same reason, deformation energy ( W ), defined as the area under the alveogram curve, decreased ( p < 0.05) in D10 (but not for D5) compared to D0. Similar results were reported for doughs with barley husk and purple sweet potato flour 26,27 …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For the same reason, deformation energy ( W ), defined as the area under the alveogram curve, decreased ( p < 0.05) in D10 (but not for D5) compared to D0. Similar results were reported for doughs with barley husk and purple sweet potato flour 26,27 …”
Section: Resultssupporting
confidence: 84%
“…Similar results were reported for doughs with barley husk and purple sweet potato flour. 26,27 The inclusion of GPP modified the gelatinization characteristics of the doughs (Table 1). GPP inclusion levels influenced the temperature of the beginning gelatinization, which increased from 63.0 to 65.0 in D0 and D10, respectively (p < 0.05).…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…In a previous study, Hong and Koh [ 21 ] stated that the baking processing method has no effect on the total phenolic content of purple sweet potato. In another study by Liu et al [ 22 ], they observed bread making substituted with purple sweet potato flour and stated that the addition of purple sweet potato flour 15% significantly increased total phenol compounds and their antioxidant activity. They reported total phenol of 224 mg GAE/100 g db.…”
Section: Resultsmentioning
confidence: 99%
“…An optimal crumb moisture level ensures a moist and tender crumb while preventing excessive dryness or sogginess [26,27]. This is crucial because moisture content affects the shelf life, softness, and overall quality of baked products.…”
Section: (B) Crumb Moisture Of Wheat-sologold Flour Composite Baked P...mentioning
confidence: 99%
“…Sample volume is an essential parameter for assessing the quality and consumer acceptability of baked products [27,34]. The volumes of baked samples: X3, Y3 and Z3 were 53.12 cm 3 , 12.32 cm 3 and 52.12cm 3 which are lower than those of X1, Y1 and Z1 but higher than values of X2, Y2 and Z2.…”
Section: (E) Sample Volume Of Wheat-sologold Flour Composite Baked Pr...mentioning
confidence: 99%